INTERRELATION BETWEEN EMOTIONAL INTELLIGENCE AND THE WAYS OF RESPONDING TO CONFLICTS IN STUDENTS -SPORT TEACHERS - H. Andonov; T. Marinov (Trakia Journal of Sciences)
The role of sports teachers is complex, often requiring them to navigate various situations. Conflict situations can arise during sports events, and their successful resolution depends on the sports educator's specific knowledge and skills supporting themin choosing the proper behavior and actions. Our research aimsto reveal the state and degree of determination between the emotional intelligence of students -sports teachers and their ways of reacting to conflicts. A total of 153 students from the Faculty of Sport and the Faculty of Pedagogy at the National Sports Academy ‘Vassil Levski’ were studied. Methods:The main research methods, adapted for Bulgaria, were: ‘The Schutte Self-Report Emotional Intelligence’ and ‘The Thomas-Kilmann Conflict Mode Instrument.’ The results were processed using variation and correlation analysis.Results:The indicators of the two tests revealed a high emotional intelligence level and harmony in reacting to conflicts among the studied. The motivation for overcoming obstacles and the ability to control emotions were leading and directly related to the participants’ attitude to collaboration, accommodation to the situation, and the manifestation of a reasonable compromise. The highest determination (74%) was between ‘Perception of own emotions and self-control’ and ‘Collaborating’ in a conflict situation. Conclusion: General emotional intelligence and all its factors are highly determined by the indicators of conflict-handling modes.